Becoming a leader for underserved patients—the importance of student run free clinics - Cheney, Ann Marie; Baltrushes, Noah; Gehlbach, Daniel; Navarro, Armando (Frontiers in Health Services, 2024)
Many students enter medical school with aspirations of expanding healthcare to underserved communities and reducing healthcare access barriers; yet they lack the leadership skills to achieve this goal. This perspective discusses the role of student-run free clinics in developing medical students’ leadership abilities—problem-solving, partnership building, planning, decision-making, and resource acquisition—to address the healthcare needs of marginalized patient populations. It also discusses how fostering leadership skills in the context of serving underserved patients also develops medical students’ structural competency and thus awareness of how inequities embedded within hierarchies and social institutions shape health outcomes. We use the example of the development of the Coachella Valley Free Clinic, a student-led and community engaged primary care clinic, to illustrate how student-run free clinics create opportunities for medical students to build leadership skills while addressing the healthcare needs of marginalized patient populations. Medical students, working alongside community health workers and federally qualified healthcare centers, devised a “pop-up” clinic model aimed at delivering care that is both culturally sensitive and linguistically appropriate, thereby addressing health disparities rooted in systemic inequality. As we argue, SRFCs create real-world settings where medical students can develop their leadership skills and understanding of inequities in health ultimately contributing to the broader goal of reducing health inequities by improving healthcare access for underserved patient populations.